Cingciripit: Permainan Anak-Anak Sunda dalam Pembelajaran Tari - Ria Sabaria (Gondang: Jurnal Seni dan Budaya, 2020)
One type of traditional children’s games originating from West Java is the Cingciripit Kaulinan. It is a children’s game that has many benefits for cognitive and gross motor development. This study aims to make observations objectively that reveal various findings from several existing data and describe them systematically. Facts and characteristics of objects and subjects, in this case, the children’s game examined in the field, are analyzed and described appropriately into one form of description in a written report. The study was conducted at Padasuka State Elementary School in Bandung, West Java. This study was conducted in August-October 2019. It employed a theoretical and methodological approach. Understanding phenomenology seeks to open hermeneutic meanings starting from Lingua (language) to philosophical interpretations of the work. This study implemented a descriptive research method with a qualitative approach. The results of the study found that there are meanings and values of Cingciripit on the meaning of the song, the meaning of the motion, and the value in the game. The dance elements in Cingciripit include motion, space, and time.